SOCIOLINGUISTIC BARRIERS AND PSYCHOLOGICAL COPING STRATEGIES AMONG ELITE UZBEK ATHLETES IN INTERNATIONAL COMPETITIONS - Abdujalilovna, Valiyeva Gulbakhor (Antis-Publisher, 2026)
Objective: This study investigates the psychological adaptation mechanisms of 22 elite athletes from the National Team of Uzbekistan when operating in a linguistically foreign environment. Method: Using a combined approach of a sociolinguistic survey and a modified V.V. Boyko methodology, the research analyzes the cognitive shift between rational and intuitive decision-making strategies. Results: Contrary to the traditional view that athletes primarily rely on intuition and reflexes, our findings reveal a dominance of the Rational Channel (85.0%) over the Intuitive Channel (32.0%). The data suggests that the language barrier acts as a stressor that suppresses emotional reactivity and activates a compensatory mechanism defined as